P454 Successful extubation in very low birth weight infants in a tertiary neonatal intensive care unit. (June 2019) - Jenkinson, A; Sweetman, D; McCarthy, LK
Abstract : Introduction: Prompt extubation of mechanically ventilated very low birth weight infants (VLBW) in the NICU, when clinically ready is in infants' best interest. It can be difficult to predict which infants will extubate successfully. No one bedside test or clinical sign has proven useful as a predictive tool. Reported rates of extubation failure in preterm infants are as high as 50%. At our level 3 NICU the decision to extubate an infant is at the discretion of the clinical team; there are no set extubation criteria. We aimed to determine the rate of successful extubation at our hospital; and to describe any clinical markers associated with extubation success or failure. Methods: This retrospective review was carried out at the National Maternity Hospital, between January 1 st and December 31 st 2017. VLBW infants with a birth weight (BW) ≤1500 g, that were mechanically ventilated and had a planned extubation attempt during their admission were included. For each individual we included data from the first extubation attempt only. Results: Of the 146 infants ≤1500 g admitted to the NICU, 56(38%) were intubated and 48(33%) had a planned extubation attempt. The mean (SD) gestational (GA) of the 48 included infants was 28(2) weeks, BW 1097(261)g. Extubation was successful in 82% of infants and was associated with higher GA and BW, and shorter duration of ventilation. At re-intubation, 80% of infants had an additional co-morbidity. Conclusion: The rate of extubation success at our NICU is higher than previously reported. There are multiple potential reasons for this including tertiary antenatal care, few outborn infants, completed courses of ANS, postnatal steroid use; or a conservative approach to extubation. A higher GA and BW, and shorter duration of mechanical ventilation were associated with extubation success.